Work Ethic as a Mirror for the Russian Orthodox Church: Sociology of Religion in Terms of Sociology of Law - Кирилл Титаев (Russian Sociological Review, 2013)
Review of Osnovnye kategorii khozyaistvennoi etiki sovremennogo russkogo pravoslavia: sociologichesky analiz [Main Categories of the Work Ethic of Contemporary Russian Orthodox Church: A Sociological Analysis] by Ivan Zabaev (Moscow: PSTGU, 2012).